Tadalafil Once a Day for Men with Erectile Dysfunction: Is It Superior than On-Demand Administration? - Dimas Tri Prasetyo; Putu Angga Risky Raharja; Ben Julian Mantiri; David Ralph Lienhardt Ringoringo; Irham Arif Rahman; Jody Felizio; Made Parulian Tambunan; Syifa Fauziah Fadhly; Harrina Erlianti Rahardjo (Interna Publishing, 2019)
Background: Tadalafil is a PDE5I which has been licensed for the treatment of erectile dysfunction (ED) since 2003, is effective from 30 minutes after administration and its efficacy is maintained for up to 36 hours. More recently, it is also given OAD in a lower dose to allow spontaneous sexual activities. However, whether OAD administration is more effective than PRN administration in improving the EF is yet to be established. This study aimed to evaluate whether OAD administration of tadalafil leads to a better improvement of erectile function (EF) in patients with erectile dysfunction (ED) compared to PRN administration. Methods: literature search of electronic database was performed through Medline, Scopus, Cochrane Library, and CINAHL databases. Cochrane Risk of Bias Tool was then employed to assess the risk of bias in each study. Results: initial literature search resulted in 231 hits, but only four studies were included in final selection. Based on our judgements, the study by Kang et al. was the most applicable in our clinical setting. This study showed that subjects who received tadalafil OAD had statistically significant higher increases of mean IIEF-EF (6.5 (SD 4.5) vs 4.9 (SD 4.2), p=0.032), proportion of "yes" responses to SEP-2 (81.8% vs 64.7%, p=0.025), and proportion of "yes" responses to SEP-3 (77.3% vs 60.3%, p=0.034). Conclusion: administration of tadalafil OAD leads to a better improvement of EF compared to PRN administration.